2018
DOI: 10.2196/mhealth.9119
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Pregnancy Apps and the Implications for Culturally and Linguistically Diverse Women: Narrative Review

Abstract: BackgroundPregnancy apps are a booming global industry, with most pregnant women in high-income countries now using them. From the perspective of health care and health information provision, this is both encouraging and unsettling; the demand indicates a clear direction for the development of future resources, but it also underscores the importance of processes ensuring access, reliability, and quality control.ObjectiveThis review provides an overview of current literature on pregnancy apps and aims at descri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
112
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 55 publications
(104 reference statements)
8
112
0
3
Order By: Relevance
“…There is an increasingly large volume of users accessing the range of health apps for female reproductive health. Yet these types of apps have previously only been studied in small samples with a focus on reviewing the information within apps [30,32,41,42], or the design and testing of novel apps [43][44][45][46][47]. Presently, the association between knowledge about female reproductive health and the use of reproductive health-themed apps has yet Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasingly large volume of users accessing the range of health apps for female reproductive health. Yet these types of apps have previously only been studied in small samples with a focus on reviewing the information within apps [30,32,41,42], or the design and testing of novel apps [43][44][45][46][47]. Presently, the association between knowledge about female reproductive health and the use of reproductive health-themed apps has yet Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the survey, 24 app using respondents self-identified that they were trying to conceive, yet 55 app using respondents were reportedly using a 'plan a pregnancy' app. There are a range of pregnancy-related apps available to accommodate for many stages throughout pregnancy (planning to conceive, trying to conceive, predicting gestation monitoring pregnancy, etc) [42], and respondents may have selected this to cover this broad range of applications. Apart from the free-text option, 'plan a pregnancy' was the only selectable option that mentioned pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite data that indicate that over 90% of women in their peak reproductive years (19-34 years of age) own a smartphone (Silver et al 2019), there are lower levels of pregnancy app use for women in low socioeconomic groups. Technology literacy, health literacy, and language barriers are suspected to be causes for the reduced use of digital health resources, including pregnancy apps (Hughson et al 2018). Likewise, as cities expand, the urban population tends to become more culturally and ethnically diverse and socioeconomic disparities can become even more pronounced.…”
Section: Digital Health Resourcesmentioning
confidence: 99%
“…Commercial apps communicating about pregnancy-related health, speci cally, are becoming increasingly common [19,20], with healthcare providers endorsing that they play a growing role in maternity care [18,19]. Using mobile health apps as a widespread form of supplementary clinical support shows promise in both increasing patient education and in narrowing the knowledge gap in health disparate communities [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the striking maternal health disparities which currently exist, the risk of further distancing health disparate communities has worrying consequences. Several studies have critically reviewed the content of pregnancy apps [20,28,29], with Thomas & Lupton (2016) nding that pregnancy and other reproductive health apps fail to be inclusive of diverse pregnant people. These kinds of ndings raise concerns of bias in the language and imagery used in pregnancy-health apps.…”
Section: Introductionmentioning
confidence: 99%